2022
DOI: 10.3389/fpsyg.2022.873247
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Intimate Partner Violence Between Emotional Dependence and Addictive Behaviours in Adolescents

Abstract: ObjectiveIntimate partner violence (IPV) has been related to emotional dependence and addictive disorders. This study aims to provide a global approach to analyse the relationship between these variables and to determine the factors underlying permanence in violent relationships.MethodsIt is a non-experimental, cross-sectional correlational design study. Participants had to have at least one dating relationship for at least 1 month to complete the questionnaire, which included the following instruments: emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Although ED is more frequent in women, research [ 42 , 48 , 49 , 50 ] also evidences that this phenomenon affects both genders, suggesting that there can be differences in the way it is experimented and in the consequences on dating relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ED is more frequent in women, research [ 42 , 48 , 49 , 50 ] also evidences that this phenomenon affects both genders, suggesting that there can be differences in the way it is experimented and in the consequences on dating relationships.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies [ 48 , 49 , 50 , 51 ] have indicated that men can also manifest high levels of dependence in their relationships, although the dynamics and manifestation of this dependence may differ. Arbinaga et al [ 48 ] found a significant link between DE and DaV among adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The doctor-patient relationship was measured with included five measurement items revised from Zhang et al ( 1 ). The scale of emotional dependence was adopted from Macia et al ( 28 ) and Wang, Zhang, Han, and Ma ( 11 ). The measure of healthcare costs was adopted from Wang et al ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…Emotional dependence refers to outcome-based emotional evaluation that is generated by patients in their interaction with healthcare services and reflects the emotional connection and bond established between patients, doctors, and online healthcare platforms ( 28 ). The perception of healthcare quality refers to the quality and effects of healthcare services, largely, the timeliness, effectiveness, and safety of healthcare services ( 29 ).…”
Section: Research Hypotheses and Model Proposalmentioning
confidence: 99%